Effect of replacing inorganic minerals with small peptide chelated minerals on production performance, some biochemical parameters and antioxidant status in broiler chickens - Kong, Jing; Qiu, Ting; Yan, Xia; Wang, Lili; Chen, Zhiyong; Xiao, Gengsheng; Feng, Xin; Zhang, Huihua (Frontiers in Physiology, 2022)
The current study was designed to evaluate if replacing inorganic trace minerals (ITM) with small peptide chelate trace minerals (SPM) affect growth performance, slaughter performance, blood and liver antioxidant status, tibia mineral deposition, and fecal mineral excretion in 817 white-feathered broilers. A total of 432 broilers (21-day-old) were randomly divided into four groups with six replicates of 18 chicks each. The four groups included inorganic trace minerals group (addition of 1000 mg/kg ITM; common practice by commercial poultry farms), three organic trace minerals groups with supplementation of 150, 300 and 500 mg/kg SPM, respectively. The experiment lasted for 30 days. The results showed that there was no significant difference in growth performance and slaughter performance among the four groups (P > 0.05). Total cholesterol in the ITM group was significantly higher than those in SPM groups (P < 0.01). Compared with the ITM group, the serum urea nitrogen in 150 and 300 mg/kg SPM groups decreased significantly (P < 0.01). Among all SPM treatments, 300 mg/kg SPM groups had the highest serum glutathione peroxidase (GSH-Px) activity (P < 0.01). The activity of copper and zinc superoxide dismutase (Cu/Zn SOD) of liver in ITM group was the lowest among the four groups (P < 0.01). The catalase (CAT) activity of liver in the 150 mg/kg SPM group was significantly higher than the ITM group and 300 mg/kg SPM group (P < 0.05). Compared to the ITM group, the iron content of the tibia was significantly increased in 300 mg/kg SPM group (P < 0.05) and 500 mg/kg SPM group (P < 0.01). Compared to the ITM group, dietary supplementation with SPM significantly reduced fecal content of zinc and manganese (P < 0.01). The 150 mg/kg SPM and 300 mg/kg SPM group had significantly reduced content of iron (P < 0.05). This study demonstrated that replacing inorganic minerals with low doses of SPM (300 and 500 mg/kg) did not negatively affect growth and slaughter performance, as well as the antioxidant status of broiler chickens. in addition, SPM can also promote mineral content in the tibia and reduce mineral content in the feces.